Frami-Software for Brazilian Jiu-Jitsu: Development and Validation of the Protocol for Technical-Tactical Analysis; [Frami-Oprogramowanie Do Analizy Brazylijskiego Jiu-Jitsu: Opracowanie I Zatwierdzenie Protokołu Analizy Techniczno-Taktycznej] - Brito, C (Idokan Poland Association, 2024)
Background. This research is characterized as an applied technological and descriptive study that addresses the following aspects: development of technical-tactical modeling, description, and correlation of actions in the context of Brazilian Jiu-Jitsu (BJJ) combat. Aims. The present study aims to create and validate the Frami software with a BJJ technical-tactical analysis protocol. Methods. From 2,607 BJJ matches, considering all weight divisions, ranked as the best in the world and qualified for the 2018 and 2019 Abu Dhabi Professional Jiu-Jitsu World Championships, 20 Jiu-Jitsu combat presentations were selected, and used in two moments (First analysis x same analysis after 24 hours). The indicators were identified in previous reports (i.e., approach phase, gripping, guard, mounting, attack/ defense phase, and low-intensity movement phase). The model was performed intra- and inter-specialist validation, p≤0.05. Results. The general average level of Reliability among all evaluators when classifying the phases of the combat and technical actions of the athletes subdivided by stage resulted in Alpha 0.90 (0.86; 0.93), classified as excellent. Conclusion. In developing the specific instrument for the BJJ, we suggested nine BJJ combat phases. Thus, this instrument is a pioneer technical-tactical tool in BJJ and could help coaches and athletes to develop new contextual training based on detailed analysis. © Yoshin Academy